A review of the reliability of biomechanical variables produced during the isometric mid-thigh pull and isometric squat and the reporting of normative data - Brady, C. J.; Harrison, A. J.; Comyns, T. M. (Sports Biomechanics, 2020)
The use of isometric strength testing, particularly the isometric mid-thigh pull (IMTP) has increased dramatically over the last decade. The IMTP and isometric squat (ISqT) provide one aspect of performance monitoring with variables such as peak force and rate of force development being derived from the force-time curve. The reliability of some of these variables is conflicting in the literature, and the reporting of the reliability is not standardised across the research. The majority of research only reports intraclass correlation coefficients with very few studies reporting coefficient of variation and 90% confidence intervals. Additionally, methods used to calculate variables from the force-time curve differ across studies. An aim of muscle strength testing is to provide normative values for specific sports, allowing coaches to distinguish between performance levels or evaluate the effects of training on performance. This narrative review aims to evaluate studies that have researched the reliability and/or reported normative data for both tests. Additionally, the testing protocols and the force-time curve analysis techniques utilised are discussed, concluding with practical applications for coaches on the uses and limitations of these tests. Results demonstrate that peak force is the most reliable measure and can be used to determine maximum strength capabilities.